2022
DOI: 10.1111/ele.14150
|View full text |Cite
|
Sign up to set email alerts
|

Heat tolerance variation reveals vulnerability of tropical herbivore–parasitoid interactions to climate change

Abstract: Assessing the heat tolerance (CTmax) of organisms is central to understand the impact of climate change on biodiversity. While both environment and evolutionary history affect CTmax, it remains unclear how these factors and their interplay influence ecological interactions, communities and ecosystems under climate change. We collected and reared caterpillars and parasitoids from canopy and ground layers in different seasons in a tropical rainforest. We tested the CTmax and Thermal Safety Margins (TSM) of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 98 publications
2
3
0
Order By: Relevance
“…Whilst duration of heat waves did not affect host emergence directly, exposing the parasitised hosts to longer heat waves increased the mortality of parasitoids, including complete mortality after 72 hours of heat waves exposed in the early life stage, leading to greater host emergence from parasitized hosts. This supports the general idea finding that parasitoids are less tolerant to heat stress than their hosts (Wenda et al, 2023, Hance et al, 2007, but emphasises that heat wave duration rather than the level of heat wave may be more important. Thus, the detrimental effects on parasitoids experiencing high temperatures for a long period of time can disrupt the trophic interactions, and suggests that pest outbreaks might be more likely if such conditions are experienced in nature.…”
Section: Discussionsupporting
confidence: 87%
“…Whilst duration of heat waves did not affect host emergence directly, exposing the parasitised hosts to longer heat waves increased the mortality of parasitoids, including complete mortality after 72 hours of heat waves exposed in the early life stage, leading to greater host emergence from parasitized hosts. This supports the general idea finding that parasitoids are less tolerant to heat stress than their hosts (Wenda et al, 2023, Hance et al, 2007, but emphasises that heat wave duration rather than the level of heat wave may be more important. Thus, the detrimental effects on parasitoids experiencing high temperatures for a long period of time can disrupt the trophic interactions, and suggests that pest outbreaks might be more likely if such conditions are experienced in nature.…”
Section: Discussionsupporting
confidence: 87%
“…While duration of heat stress did not affect the probability of host emergence directly, exposing the parasitized hosts to longer heat stress in the early life stage increased the mortality of parasitoids, including complete mortality after 72 h of exposure to heat stress, resulting in greater host emergence from parasitized hosts. This supports the general finding that parasitoids are less tolerant to heat stress than their hosts (Hance et al., 2007 ; Wenda et al., 2023 ), but emphasizes that heat stress duration and timing in particular may be fundamental to parasitoid success. Thus, the detrimental effects on parasitoids experiencing high temperatures for a long period of time can disrupt trophic interactions, and suggests that pest outbreaks might be more likely if such conditions are experienced in nature (Moore et al., 2022 ).…”
Section: Discussionsupporting
confidence: 86%
“…First, one can extend this finding to food web / multitrophic scales to see how temperature-mediated change would propagate through trophic cascades. For example, a very recent study 38 showed variation in maximum thermal tolerance limits reduced parasitoid-herbivore food web stability in a climate change context. Second, as observed in a recent study 39 , one could explore the eco-evolutionary feedback mechanisms specific to four TC components individually.…”
Section: Discussionmentioning
confidence: 99%